STASIUN KERETA API BOGOR, JAWA BARAT ABAD KE-19 HINGGA KE-20: KAJIAN ARKEOLOGI INDUSTRI - Ilham, Rakan Amir; Nasution, Isman Pratama (Multikultura, 2025)
Bogor railway station is a railway building in the city of Bogor that has played a role in community activities since the 19th century. This research uses an industrial archaeology approach in reconstructing social and economic activities as well as the development of railway technology and operations. This research was conducted through seven stages, namely formulation, implementation, data collection, data processing, data analysis, data interpretation, and publication. This research produced an overview of railway activities such as the development of locomotive types, the division of social classes at the station, as well as the political, tourism, and economic influences of this station.